Zurtasht nāmah : Shat va Ḵẖashur Zartasht ke ḥalāt-i zindagī aur unkā mazhab - Ḵẖalīlurraḥmān, Muḥammad, 1854-1924 (SAMP early 20th-century Indian books project, 1904)
On the life of Zoroaster and his religion.